The associations between depressive and anxiety symptoms, body image, and weight in the first year postpartum: a rapid systematic review. (1st January 2018) - Hartley, Eliza; Hill, Briony; McPhie, Skye; Skouteris, Helen
Abstract: Objective: The aim of this study was to conduct a rapid systematic review of the evidence of associations between postpartum depressive symptoms, anxiety symptoms, body image and weight status in the first 12 months post birth. Background: The postpartum period places the mother and infant at risk of a number of negative health outcomes. Mental health conditions such as depression and anxiety are common in the postpartum, as are poor body image and excessive weight retention as women adjust to their post pregnancy body. However, the associations between body image, weight status and psychological distress are not currently well understood. Methods:   Articles in English, published between 2006 and 2017, involving singleton pregnancies of normally developing infants and maternal depression or anxiety were eligible for this systematic review. Results:  From the total of 1805 articles located, 12 were identified as relevant and were subsequently reviewed in full. In the nine studies of depressive symptoms, body image or weight status, four found a significant relationship . Significant associations were not found in the three studies investigating postpartum anxiety symptoms, body image or weight. Body dissatisfaction was associated significantly with poorer postpartum weight status in all nine studies. Conclusions: Further research is needed to determine the nature of the relationships between body image, weight status and depressive and anxiety symptoms across the first year after birth. This information will assist health professionals to promote healthy lifestyle behaviours in the postpartum, as well as inform clinical interventions that target behaviour change to prevent the worsening of these issues and related negative outcomes.